Comprehensive Review of Nursing Education, Mental Health Advocacy, And Evolving Practices - Al malki, Saad Safran; Al sheheri, Maryam Thabet Abdullah; Alsiddiq, Nouf Yahyi Abdo; Mashat, Egbal Atiya; Thani, Fatima Ahmad; Al Zahrani, Khadran Hezam Saeed; Al-Mawlid, Zain Dakhil Saleh; Alsharif, Amani Ali Hasan; Alkhudaydi, Taher Abdullah Abdulrahim; sait, Abrar Mohamad yousef; Ganeem, Hisham Abdullah (Journal of Ecohumanism, 2024)
More changes have been observed in nursing education over the years, including promoting health advice, advocacy for mental health, and other new changes. This paper will review the effectiveness of nursing education on mental health advocacy, identify changing practices across this field, and discuss the problems and possibilities implicated in enhancing mental health care through changes in nursing education. These discoveries raise the question of including mental health educational programs in nursing education, improving the nurses’ competencies, and increasing the advocacy for mental health in healthcare facilities and societies. The review also analyses how emerging trends, including telehealth, cultural competence, and interprofessional practice, inform mental health care. Then, drawing on available data for the given priority areas, the paper gives recommendations for future improvement of nursing education and practice to meet different populations' identified mental health needs.